IMPLEMENTASI KEBIJAKAN GREEN AND CLEAN PADA DINAS KEBERSIHAN DAN PERTAMANAN KOTA PALU - Jaenudin, Muhajirin (Katalogis, 2015)
This study aims to determine how the Policy Implementation Program Green and Clean At the Department of Hygiene and Palu studied based model of policy implementation George Edward III on aspects of communication, resources, disposition and bureaucratic structure. This type of research is qualitative research with decision-informant by purposive sampling or sampling on purpose and the number of selected informants 9 people. The results showed in policy implementation Green and Clean Program at the Department of Hygiene and Palu City has not run well, because 1). Communication factors that do not evenly throughout society melainka only certain region. 2). Resources in terms of factors to understanding the staff of the Green and Clean, not all staff sections to understand what needs to be done in implementing the Green and Clean. 3). Bureaucratic Structure Factors which Prusedur Operational Standards on revenue funding problems are minimal. 4). In terms of attitude Implementation of the interview that komentmen of the Department of Hygiene and Palu city is good enough, where the Department of Hygiene and Palu City always conduct an intense evaluation of the Green and Clean in Palu